Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021) 2021
DOI: 10.22323/1.395.0609
|View full text |Cite
|
Sign up to set email alerts
|

Study of the gamma-ray state changes of PSR J2021+4026 with Fermi-LAT

Abstract: The peculiar radio-quiet PSR J2021+4026, in the Gamma Cygni supernova remnant, is one of the brightest of the over 250 pulsars detected by Fermi-LAT. It is unique in being the only known isolated gamma-ray pulsar to undergo abrupt flux changes, which are also simultaneous with spin-down variations. The first change was observed by Fermi-LAT in October 2011, and it was followed by a recovery over a timescale of 100 days around December 2014. A second change occurred in February 2018. In the last few years, PSR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…This pulsar experienced a decrease in flux near 2011 October 16 (Allafort et al 2013 ) that corresponds to the end of the high-γ -rayflux state reported in Table 1 . In addition to that dimming event in 2011, further γ -ray state changes of PSR J2021 + 4026 in 2014 and 2018 were reported by Fiori et al ( 2022 ). We found the flux changes in 2014 December and 2018 February with significances of 10.3 σ and 10.4 σ each confirming the result reported by Fiori et al ( 2022 ).…”
Section: Psr J2021 + 4026supporting
confidence: 87%
See 2 more Smart Citations
“…This pulsar experienced a decrease in flux near 2011 October 16 (Allafort et al 2013 ) that corresponds to the end of the high-γ -rayflux state reported in Table 1 . In addition to that dimming event in 2011, further γ -ray state changes of PSR J2021 + 4026 in 2014 and 2018 were reported by Fiori et al ( 2022 ). We found the flux changes in 2014 December and 2018 February with significances of 10.3 σ and 10.4 σ each confirming the result reported by Fiori et al ( 2022 ).…”
Section: Psr J2021 + 4026supporting
confidence: 87%
“…In addition to that dimming event in 2011, further γ -ray state changes of PSR J2021 + 4026 in 2014 and 2018 were reported by Fiori et al ( 2022 ). We found the flux changes in 2014 December and 2018 February with significances of 10.3 σ and 10.4 σ each confirming the result reported by Fiori et al ( 2022 ). They also reported that PSR J2021 + 4026 was in its low flux state from 2018 February 2 to 2020 May 26.…”
Section: Psr J2021 + 4026supporting
confidence: 87%
See 1 more Smart Citation
“…We ran the binned likelihood analysis on each interval separately, keeping all the spectral parameters free to vary. This was not possible our previous report due to a different choice of the spectral model [9]. Therefore, it represents an improvement in our capability of characterizing spectral variations.…”
Section: Spectral Variabilitymentioning
confidence: 83%
“…We report on an updated LAT monitoring activity of PSR J2021+4026 that allowed the detection of a new mode change occurred around June 2020. This work also brings improvement to the spectral analysis compared to our previous report [9]. The manuscript is outlined as follows.…”
Section: Introductionmentioning
confidence: 96%